Porphyria Cutanea Tarda with Constrictive Pericarditis: A Rare Association - Kaur Jasleen; Nidhi Sharma; Jyotika Kalsy; Mughda Sharma (Case Reports in Dermatological Medicine)
Porphyria cutanea tarda(PCT) is characterised by photosensitivity and bulla formation on photoexposed parts which heals with scaring and pigmentation. PCT is frequently associated with diabetes mellitus, lupus erythematosus and hepetitis C virus infection. We are reporting and Indian patient of PCT associated with pericarditis which is very rare.